2019
DOI: 10.1002/ange.201911875
|View full text |Cite
|
Sign up to set email alerts
|

The Core Fucose on an IgG Antibody is an Endogenous Ligand of Dectin‐1

Abstract: The core fucose,amajor modification of N-glycans, is implicated in immune regulation, such as the attenuation of the antibody-dependent cell-mediated cytotoxicity of antibody drugs and the inhibition of anti-tumor responses via the promotion of PD-1 expression on Tc ells.A lthough the core fucose regulates many biological processes,n oc ore fucose recognition molecule has been identified in mammals.Herein, we report that Dectin-1, ak nowna nti-b-glucan lectin, recognizes the core fucose on IgG antibodies.Acomb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…This latter phenomenon has inspired the development of next-generation therapeutic monoclonal antibodies that more effectively engage FcgRIIIa and demonstrate superior antibody-dependent cellular cytotoxicity (ADCC) 11,12 . Recently, dectin-I was identified as the first endogenous lectin that specifically recognises core fucose 13 . Collectively, these and other findings demonstrate that FUT8 plays a central role in modulating the activity of many cell-surface receptors.…”
Section: Introductionmentioning
confidence: 99%
“…This latter phenomenon has inspired the development of next-generation therapeutic monoclonal antibodies that more effectively engage FcgRIIIa and demonstrate superior antibody-dependent cellular cytotoxicity (ADCC) 11,12 . Recently, dectin-I was identified as the first endogenous lectin that specifically recognises core fucose 13 . Collectively, these and other findings demonstrate that FUT8 plays a central role in modulating the activity of many cell-surface receptors.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it should be noted that the role of N-glycan modifications can be different between proteins. We reported that dectin-1 specifically recognized core fucosylated IgG and did not interact with other core fucosylated proteins, suggesting that core fucose on IgG has specific physiological functions [82]. The role of N-glycans on distinct proteins is an important topic for future work.…”
Section: Functional Analysis Of N-glycans On Glycoproteinsmentioning
confidence: 95%
“…STD-NMR using a fluorine derivative (2D STD-TOCSYreF) indicated that the mannose on the α1,3-branched chain was more strongly recognized by PSA than the mannose on the α1,6-branched chain [81]. In addition, dectin-1, which recognizes fungal β-glucan, was found to recognize core fucose on immunoglobulin (IgG) [82]. STD-NMR analysis indicated that dectin-1 interacted not only with core fucose but also with an Fmoc group attached to the amino group of asparagine introduced at the reducing end.…”
Section: Analysis Using Nmrmentioning
confidence: 99%
“…Dectin-1, Man receptor, and DC-specific intercellular adhesion molecule 3 (ICAM3)-grabbing non-integrin (DC-SIGN) [ 20 ] can recognize Fuc in carbohydrate patterns, but their specificity differs. Dectin-1 is better known as a receptor for yeast β-glucans, zymosan, and laminarin [ 20 ], but it can recognize the core 1,6-Fuc on immunoglobulin G (IgG) in vitro [ 21 ]. The Man receptor has two separate C- and R-type lectin motifs: the first binds terminal Fuc, Man, or N -acetyl- D -glucosamine (GlcNAc); the second binds glycans with 3- or 4- O -sulfated N -acetylgalactosamine (GalNAc), or 3- O -sulfated Lewis x (Le x )/Le a [ 22 ].…”
Section: Recognition Of Bacterial Surface Antigensmentioning
confidence: 99%